The neuroanatomical and neurochemical basis of apathy and impulsivity in frontotemporal lobar degeneration. (August 2018) - Passamonti, L; Lansdall, CJ; Rowe, JB
Highlights: Apathy and impulsivity are common consequences of frontotemporal lobar degeneration syndromes. Common frontostriatal loops mediate different modes of apathy and impulsivity across diagnoses. The noradrenergic system is a promising therapeutic target for apathy and impulsivity. Abstract : Apathy and impulsivity are common and often coexistent consequences of frontotemporal lobar degeneration (FTLD). They increase patient morbidity and carer distress, but remain under-estimated and poorly treated. Recent trans-diagnostic approaches that span the spectrum of clinical presentations of FTLD and parkinsonism, indicate that apathy and impulsivity can be fractionated into multiple neuroanatomical and pharmacological systems. These include ventral/dorsal frontostriatal circuits for reward-sensitivity, response-inhibition, and decision-making; moderated by noradrenaline, dopamine, and serotonin. Improved assessment tools, formal models of cognition and behavior, combined with brain imaging and psychopharmacology, are creating new therapeutic targets and establishing principles for stratification in future clinical trials.